SOLUSI PENCARIAN N-PUZZLE DENGAN LANGKAH OPTIMAL : SUATU APLIKASI PENDEKATAN FUNGSIONAL - Wijanarto Wijanarto Wijanarto (Semantik, 2011)
This paper aims to determine a more optimal search techniques on a case study of n-puzzle problem solving. Some algorithms are in review as breadth-first search, depth-first search, hill-climbing, beam, best-first searching and optimization with A * (A-Star) search becomes case study in simulated using a functional approach. Test simulation is based on the difficulty level of the initial state that is given from the category configuration easy, medium, hard and ugly, the calculation of the amount of expansion produced by each algorithm are discussed, as well as the time profile (report-time) of the design solution in proposing, show that the search with a * optimization method gives optimum results on n-puzzle solving compared to all other algorithms. By understanding the heuristic search algorithm is expected to help resolve the problem optimally is based on the case other than a puzzle.Keywords : A Star, Heuristic, N-Puzzle, Search, functional